Effects of field warming on a High Arctic soil bacterial community: A metagenomic analysis - Lim, P.P.J.; Newsham, Kevin K.; Convey, Peter; Gan, Han Ming; Yew, Wen Chyin; Tan, Geok Yuan Annie (Indian Academy of Sciences, 2018)
Soil microbial communities in the Arctic, one of the most rapidly warming regions on Earth, play an important role in a range of ecological processes. This report describes initial studies of natural soil bacterial diversity at a High Arctic site on Svalbard, as part of a long-term field environmental manipulation study. The impact of increased soil temperature and water availability on soil microbial communities was investigated. The manipulation experiment, using open-top chambers, was installed in late summer 2014, and the soils were sampled soon after snow melt in July 2015. High throughput sequencing of 16S rRNA genes showed relatively uniform diversity across the study area and revealed no significant initial effect of treatments on bacterial communities over the first 10-month autumn-winter-spring manipulation period.